Aptitudes and performance prediction in secondary technical-professional education (EMTP). Bases for a student selection process - Frez De-Negri, Guillermo (Revista de Psicología, 1994)
Currently, most of the Professional Technical High Schools do not have student selection processes. Only some carry out an admission process. In general, the selection processes and instruments have not been evaluated, so there is no data on the results of these procedures and instruments. The minimum requirement for an admission process, in terms of procedures and instruments, is a moderate ability to predict performance in the following year of study in Vocational Technical Education. The student selection procedure could consider aspects such as: (a) demographic variables (educational level of the parents); (b) previous academic performance (average grades); (c) personal variables (aptitudes, interests and personality).